ANTHROPOCENTRIC INTENTION OF HESYCHAST AND SUFISTIC PRACTICES OF FREEDOM PERSONAL DEVELOPMENT - Yurii Y. Semchuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The Purpose is to analyse problems of individual freedom in mystical currents of Hesychasm and Sufism comprehensively in the territory of Ukraine. It deals with issues of Hesychasm and Sufism origin, mystical practices features and their overflowing borrowing on the way to Truth by God finding. Methodology. With a view to the reconstruction of a holistic world view of the desert in their deification of personal freedom, the author uses methodology of humanitarian analysis (analysis and synthesis, comparison, abstraction, generalization), and the phenomenological method – the study specifics of the mystical way of knowing reality and comparative method − the study and comparison of different types of mystical-religious movements in the synthesis of the history of philosophy, philosophy of religion, psychology, phenomenology and the history of religion. Scientific novelty. Watching the life of the monks Optina Pustyn can trace the genesis hesychast tradition from the time of Paisius Velichkovsky. The influence and the use of spiritual advisors fundamental hesychast texts "Philokalia" in secular name and in the empyreal world alike are researched. It is proved that in the spiritual practices of Hesychasm and Sufism Set the true path to God. The mystics’ efforts in aspiration of perception of the Truth were reconstructed, as in Christian practices of an unexpected irradiation of cognition Omnipresent and in the knowledge of Jehovah in Sufism through «gentle-hearted message» which is opened to receiving spiritual vision and the gift of God without volitional intentions of the observer. Conclusions. The author concludes that despite the existence of schools and practices, personal manifestation of union with God through the freedom of own will devoted in listening of spiritual life – own heart, is dominant in Hesychasm and Sufism mystical currents. The main secret of mystics was not a transfer of theoretical knowledge through the generations, but the apparition of truth through his own aspiration to knowledge, in the unbearable austerity initiation experiences obtained enlightenment, happiness deification, the anguish of love. This barrier was the form of sense that needs to be empathized but it is impossible to learn.